Inequalities in the private funding of public schools: parent financial contributions and school socioeconomic status. (2nd January 2020) - Rowe, Emma; Perry, Laura B.
ABSTRACT: Parent involvement in their child's schooling is routinely celebrated and emphasised in government education policy in many countries. We take a critical lens to examining parent involvement by investigating voluntary parent fees in public secondary schools, and how these fees are patterned by school socioeconomic status (SES). In Australia, where this study is located, public schools may request 'voluntary' fees from parents to enhance education programmes and facilities. As public schools are increasingly situated in a competitive market, this has arguably augmented pressure for schools and their communities to generate funds. Our findings show large inequalities between public schools, with high-SES schools enjoying more than four times parent-generated income than low-SES schools. Parent financial contributions are a form of structural inequality that benefits socially advantaged students and schools, potentially serving as both a cause and consequence of socially segregated schooling. We conclude with recommendations for policy.